Analisis Strategi Pemasaran Mixue Panglima AIM Pontianak Timur Kota Pontianak - Astuti, Diah Tri; Firayanti, Yuni; Saputra, Edy Suchmawan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research dilator after the research sees that in the era of globalization today demands for every franchise to continue to be able to act inappropriately and quickly in the face of the uncertainty of the competitive environment turning into an increasingly stringent competitive force that many companies especially franchise companies experience because companies like this are constantly expanding their marketing territory. This study aims to analyze the effectiveness of the 4p marketing mix strategy (product, price, promotion, place) used by Mixue to improve its competitive advantage on product sales. Qualitative research is a method of research based on the philosophy of post-positivism or interpretative, used to minimize the condition of natural objects, in which the researcher is the key instrument. Data collection techniques are triangulated (combination of observations, interviews, documentation. The results of the research carried out at the Mixue Aim Pontianak East Pontianak indicate that the marketing strategy uses the marketing mix (4p) product (product), that is, buying the quality of the product and creating new innovations for its product, price (price) at an affordable price that can be purchased by all middle up and middle down sectors, promotion (promotion) marketing strategy is the most effective is the promotion, promotion that is done by the mixue through social media, discount or promo, place (place) strategic location and easily accessible. Thus, marketing mix that is used by the Mixue Aim Pontianak east Pontianak, especially products, price, place, and promotions, is very effective in increasing the volume of sales and dining customer loyalty.